ANALYSIS OBSTACLE FACTORS OF LECTURERS’ RESEARCH RESULT PUBLICATION - Diyah Yuli Sugiarti (Jurnal Visipena, 2017)
This research aims is to raise awareness of lecturers in publicaton of research results to the variety of Journal. This study used a qualitative approach. Data was taken from a random sample of some lecturers in UNISMA Bekasi city . Research result found out that there are only 5% lecturers that have been published research results routinely, this conditions is very low level. The low level of awareness publication of research results lecturers is caused by: 1) the lack of lecturers research, 2) the lack of writing journal skills, 3) the lack of mastery of English, 4) inactive in looking for journal in sites, 5) the lack of information on seminar or conference events to send journal and to do presentation, 6) lack of incentives from institutions.